ANALISIS KINERJA KARYAWAN DAN FAKTOR YANG MEMPENGARUHI KINERJANYA PADA BANK “ABC” MEDAN - SUDARSONO SUDARSONO; ADHI SURYA HARAHAP; SABARITA TARIGAN; DARWIN SH DAMANIK (JURNAL ILMIAH KOHESI, 2023)
Bank “ABC” provides equal opportunity to all employees to improve performance and career development of employees. Realization card products during the period 2018 to 2021 per cluster in Medan is not achieved consistently, it is certainly not in accordance with the company's expectations. This is certainly not expected the company. Results of previous studies show that the performance of the employees affected by organizational commitment, compensation, motivation, and competence. The purpose of this study was to determine the effect of each of these factors on the performance of employees. Type of research is correlational research and sampling techniques based on simple random sampling with a sample size of 60 respondents. Analysis of the data used is multiple regression analysis. The results showed that the performance of employees of Bank ABC at 63,4% influenced by the four independent variables namely compensation, competencies, motivation and organizational commitment.